The trials and tribulations of constitutionalism and the constitution-making process in Zimbabwe. (1st January 2012) - Mapuva, Jephias
Constitutionalism in Zimbabwe has been characterised by controversy with citizens getting a raw deal. The colonial era was characterised by deprivation of basic rights and civil liberties. A plethora of constitutions were established to try and create a semblance of black representation. The post-colonial era was informed by governance structures provided by the Lancaster House Constitutional document which was a surrender document that brought the protracted liberation struggle to an end. The vagaries of the Lancaster House Constitution lived to haunt even those who fought for the country, leading to an expression of dissatisfaction with its contents. After successive indecisive elections conducted under the Lancaster House Constitution, the political and economic crises of 2008 led to an impasse and the signing of the Global Political Agreement which gave birth to the Inclusive Government. This paper will explore the general theory of constitutions from the Aristotelian classical perspective. Thereafter, the paper will also provide an overview of the concept of constitutionalism, followed by the case of Zimbabwe from the colonial era and the various constitutional documents that existed. The recent political development and the role of civil society herein represented by the National Constitutional Assembly (NCA) will be presented and how the civic group has articulated the constitution reform debate since its inception in 1997.